Concept of Kriyakala Mentioned in Sushruta Samhita - Pankaj Singh; Shivani Mahajan; Ketan Mahajan; Kamal Sharma; Alok Singh (AYUSHDHARA, 2025)
In Ayurveda, a diagnosis is made based on the nature of the phenomenon rather than the name of the illness. This phenomenon is explained in terms of each patient's Samprapti, which consists of components related to Dosha, Dushya, and Adhishtana. Dosha and Dushya play a major role in the pathophysiology of the illness. The term "Shat Kriyakala" describes the stage of a pathological process in which a doctor can intervene by using the most appropriate medication and treatment method, stopping the illness process's advancement. The 21st chapter of Sushruta Samhita Sutrasthana has a detailed explanation of Shatkriyakala by Acharya. Sanchaya, Prakopa, Prasara, Sthansamshraya, Vyaktavastha, and Bhedavastha are the six phases of Shatkriyakala. In the twelfth chapter of the Astang Sangrah Sutrasthana, Vagbhat explains the Ritu Kriya Kala. There are just three: Chaya (1), Kopa (2), and Prashama (3). The influence of being is what causes these three stages of Doshas. People will return to their normal state if they follow the current ritual routine. At that point, using his intelligence and understanding to recognize the vitiated Dosha situation, Kriya Kala assists the doctor in choosing a course of therapy.